Use of ICT in decision making of agricultural marketing: Factors determining of farmers’ involvement: Use of ICT in agricultural marketing (Journal of the Bangladesh Agricultural University, 2019)
The paper investigated the magnitude of social parameters’ impacts on effective use of Information and Communication Technology (ICT) in agricultural marketing by the farmers. In addition, how farmers identify information sources and how they access to those sources in selected areas of Jamalpur district were also examined. Purposive sampling method was used in this investigation and data were collected from eighty farmer’s thorough survey questionnaire.  Descriptive statistics, Likert scale and multivariate regression model were used to analyze the data. Multivariate regression model was specified and estimated to identify the factors affecting use of ICT by farmers. The outcome of this study highlights important factors for the use of ICT. It is evident from the findings that the users of ICT are getting better quality information and are hence making significantly better decisions on all aspects of agricultural marketing. Regression analysis revealed that two factors i.e. cultivated land of farmers and level of education were the important factors of using of ICT by farmers. Modern ICT tool such as mobile phone was the most used device by the farmers due to low price and availability. They collected most of the information regarding the marketing activities of their produce by mobile phone from other progressive farmers, traders and agricultural extension workers. Social imperative findings of this paper might be helpful for the policy maker to emphasis on further extension of mobile phone based agricultural marketing information system in Bangladesh.J. Bangladesh Agril. Univ. 17(2): 226–231, June 2019